Materials Research for Manufacturing An Industrial Perspective of Turning Materials into New Products - Madsen, Lynnette D.; Svedberg, Erik B.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book is about applied materials research in industry. It presents various important topics and challenges and gives guidance to materials researchers who move to industry. The book focuses on the materials manufacturing issues for industrial application. It deals with developments and challenges in traditional materials areas, such as metals and ceramics, and new opportunities that have risen from nanotechnology and additive manufacturing. The chapters, written by senior people from large companies, include successful manufacturing undertakings, several distinct and unresolved manufacturing challenges, with the focus on approaches, timelines and the skills needed for future company research and development. The book provides a cross-section of current and future approaches valuable for new employees and academics working in industry.
Advanced Ceramics for Energy Applications -- Challenges Facing the Commercial Transport Industry -- Investments, Innovation, and Sustainability -- Materials and Technical Achievement -- An Aerospace Perspective -- Manufacturing of Advanced Refractory Technologies -- Inventing the Future with New Materials -- Advances in Glass Strength and Its Impact on Society -- From Academia to the Business.
Keywords: Building materials; Industrial engineering; Production engineering; Physics; Ceramic materials; Metals; Structural Materials; Industrial and Production Engineering; Applied and Technical Physics; Ceramics; Metals and Alloys